SHEAR STRENGTH OF PORCELINITE AGGREGATE REINFORED CONCRETE BEAMS - Farhan Hadeed, Ali; I. Aziz, Kahlil; A. Slaby, Ayad (Iraqi Journal of Civil Engineering, 2008)
Research in Iraq has expanded in the field of material technology involving the properties of the light-weight concrete using natural aggregate. Research work on porcelinite concrete has been carried out in several Iraqi Universities. However , despite the great practical importance of such concrete in construction fields ,very limited amount of work has been carried out to investigate the (shear strength) of structural light-weight aggregate concrete , therefore it is important to study the properties and their structural behavior. In this work an attempt is made to study shear strength of porcelinite reinforced concrete beams without (stirrups). The results have been compared with the results predicted by the equations of International codes, such as ACI 318M-02, BS-8110 codes and with some authors' equations as for, Hanson. The experimental results also have been compared with results obtained from normal weight concrete specimens that had been prepared for this purpose. The study mainly deals with the structural behavior of porcelinite reinforced concrete beams without stirrups, especially the shear strength, besides, the short-term deflection, strain and cracks. The variables are, compressive strength ranging between (23.0-29.8) MPa and reinforcement percentages ranging between (0.0174-0.0307). A total of 12 beams are tested; (9) are light weight concrete beams without stirrups and (3) are normal weight concrete beams, also without stirrups. The dimensions of all those beams are 135 * 260 * 1800 mm. The structural results more often, give values 2.9 times more than that of (ACI-02)